ANALISIS NILAI TUKAR RUPIAH DAN IMPLIKASINYA PADA PEREKONOMIAN INDONESIA: PENDEKATAN ERROR CORRECTION MODEL (ECM) - Imamudin Yuliadi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
The changing of exchange rate is due to interaction between economic factors and non-economic factors. The aim of this research is to analyse some factors that affect exchange rate and their implications on Indonesian economy. Analytical method used in this research is explanatory method is to test hypothesis about simultaneous relationship among variables that research by developing the characteristics of verificative research by doing some testing at every step of research. We used secon-dary data taken from BI, BPS, World Bank and IFS. We used error correction model (ECM) to analysis between independent variable and dependent variable in both the short run and long run. The result of this research shows that ratio between domestic interest rate and international interest rate did not affect negative and significantly to exchange rate. Capital flow affected negative and significantly. Balance of payment affected negative and significantly. Money supply affected positive and significantly. According ECM method that used in this research shows that the methodology is good to analyse because the magnitude of ECT is accept.